For balanced nutrient systems - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The International Institute for Tropical Agriculture (IITA) and the University of Leuven (KU Leuven), Belgium, are co-organising an international symposium on Balanced Nutrient Management Systems for the Moist Savanna and Humid Forest Zones of...